Perception of fast time fluctuations in the sound level by persons with a cochlear implant - KWIATKOWSKI, Rafał; HOJAN, Edward; SZYFTER, Witold; FURMANN, Anna; HOJAN-JEZIERSKA, Dorota (Archives of Acoustics, 2008)
The paper presents results of scaling of loudness changes of natural sounds for persons with a cochlear implant by the so-called NSLE method. The possibilities of the use of this method of loudness scaling of natural sounds in the rehabilitation of persons with a cochlear implant have been analysed.